Applied theatre evaluations as technologies of government: A critical exploration of key logics in the field. Issue 1 (1st January 2017) - Freebody, Kelly; Goodwin, Susan
This article aims to raise new questions for the field through the analysis of a set of applied theatre programme evaluation documents. The analysis of these three documents was undertaken using Bacchi's (2009) 'What's the problem represented to be?' (WPR) approach. This approach is increasingly being used for the critical analysis of public policy and social programme documents in a wide range of policy fields, but is not commonly utilized in the field of applied theatre. The WPR approach, it is argued, enables critical scrutiny of taken-for-granted representations of what applied theatre does, or can do, about social 'problems'. Analysing applied theatre programme evaluation documents as representations of social 'problems' provides an opportunity to explore some of the deep-seated logics at work in the field.